ABC transporters and G protein-coupled receptors: perspectives for novel anti-cancer drugs - Adamska, Aleksandra (Curtin University, 2019)
Pancreatic Ductal Adenocarcinoma (PDAC) is a very aggressive disease with high mortality rates and lacking effective therapeutic approach. Therefore, it is pivotal to develop novel treatments to improve the grim prognosis of patients. In my PhD project, I demonstrated the existence of an ABCC3-LPI-GPR55 loop in PDAC which activation boosts PDAC progression. Importantly, the pharmacological potential of this loop was demonstrated both in vitro and in vivo PDAC models paving a way to clinical trials.